The raman spectroscopy, photoluminescence and photocatalytic activity of the zinc tungstate - Marhabaeva, A.A.; Abdullin, Kh.A.; Lisitsyn, V.M.; Nemkaeva, R.R. (Recent Contributions to Physics, 2018)
In this paper, the result of obtaining powder tungstate ZnWO4 is presented. Powders were prepared by two methods: the hydrothermal synthesis at a temperature of about 95°C at atmospheric pressure followed by heat treatment and powder synthesis in autoclave at a temperature of 180°C and at pressure above atmospheric. The structural features of the synthesized powders were studied, the Raman spectra and photoluminescence spectra, photocatalytic properties of the ZnWO4 obtained after synthesis and subsequent annealing in air were studied. There are relation between morphology and properties of the samples with the technological conditions of synthesis and subsequent annealing temperature. To obtain the polycrystalline phase of ZnWO4 at synthesis at 95°C was required additional annealing up to 500-600°C, while the synthesis at 180°C leads to the production of a polycrystalline ZnWO4 phase. A significant photocatalytic activity of synthesized materials in the decomposition of the test substance under the rhodamine lighting.